A systematic review of psychosocial interventions to improve quality of life of people with cancer and their family caregivers - Gabriel, Israel (Nurs Open, 2020)
AIMS: To review the characteristics and effectiveness of psychosocial interventions on quality of life of adult people with cancer and their family caregivers. DESIGN: A systematic review using PRISMA guidelines. METHODS: Seven databases were searched from 2009–2019 using key terms. Included studies were assessed using the Quality Assessment Tool for Quantitative Studies. RESULTS: 1909 studies were retrieved with 12 studies included, involving 3,390 patients/caregivers. Interventions aimed to improve communication, behaviour change and setting short‐term goals. Duration of interventions varied from 4–17 weeks. Highest benefit was gained from telephone interventions. Interventions based on interpersonal counselling appeared more effective than other approaches. Studies predominantly focused on psychological, physical and social domains of quality of life. Spiritual well‐being received relatively little attention. A paradigm shift is needed to develop psychosocial interventions that incorporate spiritual well‐being. More research is needed in developing countries.